2022
DOI: 10.30541/v44i4iipp.1135-1150
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between Population and Environmental Degradation

Abstract: Economic development and population growth in the poor areas of the earth is a subject of an essential concern for the environmental economists. Developing countries are facing and suffering by the serious problem of high population growth which is causing environmental degradation. A rapidly growing population exerts pressure on agricultural land and raises demand for food and shelter which encourages the conversion of forest land for agricultural and residential uses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…One of them is population density which has a positive impact on the decline in environmental quality. It is supported by research conducted by Zuhri in Indonesia (2014) and Ahmad et al (2005) in Pakistan. The previous research shows that a higher population density in an area has a negative impact on the environmental quality.…”
Section: Introductionmentioning
confidence: 88%
“…One of them is population density which has a positive impact on the decline in environmental quality. It is supported by research conducted by Zuhri in Indonesia (2014) and Ahmad et al (2005) in Pakistan. The previous research shows that a higher population density in an area has a negative impact on the environmental quality.…”
Section: Introductionmentioning
confidence: 88%
“…The evident outcome of high density of population within a small area is gradual decline in agricultural land due to its conversion to other uses (Ahmad et al, 2005). Therefore, feeding a very high population will be a challenge for the coming days for Bangladesh with a very small arable land per person.…”
Section: Discussionmentioning
confidence: 99%
“…Developing countries are facing serious problem of accelerating environmental degradation, with a rapidly increasing population. Ahmad et al (2005) found a co-integrating vector, which indicates a strong long relationship between demographic and environmental indicators. The results suggest that both population growth and population density raise CO 2 emissions over the long term and reflect a potentially harmful environmental effect for the population.…”
Section: Review Of Literaturementioning
confidence: 91%